â€œWriting in Search of a Homelandâ€: Re-creating Home in Meena Alexanderâ€™s Fault Lines: A Memoir - Dalal, Universiti Teknologi MARA, Malaysia, Sanghamitra (Asiatic: IIUM Journal of English Language and Literature, 2015)
In this article I investigate Indian-American author Meena Alexander’s autobiographical memoir, Fault Lines (2003). Multiply fragmented by relocations and remembrances, flights and motions, Alexanderâ€Ÿs memoir is relentlessly marked by her ceaseless quest for stability â€“ at home and in exile. As she repeatedly emphasises her irresistible impulse to write since her childhood and particularly to write her self, I will attempt in this article to explore the importance of self-writing in diaspora. Consequently, I will argue that diasporic self-writing not only induces a therapeutic wholeness amidst disjunction and displacement, but also effectively de-creates and re-creates shifting and changing paradigms of the diasporic homes.